Middle English Medical Recipes and Literary Play, 1375-1500 - Bower, Hannah (Oxford University Press, 2022)
This volume is the first detailed, book-length study of Middle English medical recipes in their literary, imaginative, social, and codicological contexts. Analysing recipe collections in over seventy late medieval manuscripts, this book explores how the words and structures of recipes could contribute to those texts' healing purpose, but could also confuse, impede, exceed, and redefine that purpose. The study therefore presents a challenge to recipes' traditional reputation as mundane, unartful texts written and read solely for the sake of directing practical action. Crucially, it also relocates these neglected texts and overlooked manuscripts within the complex networks forming medieval textual culture, demonstrating that-though marginalized in modern scholarship-medical recipes were actually linguistically, formally, materially, and imaginatively interconnected with many other late medieval discourses, including devotional writings, romances, fabliaux, and Chaucerian poetry. The monograph thus models for readers modes of analysis and close reading that might be deployed in relation to recipes in order to understand better their allusive, fragmentary, and playful qualities as well as their wide-ranging influence on medieval imaginations.